Annual Plan West Bengal 1997-98 Volume-I - Planning Commission (Planning Commission, 1997)
The proposals for the Annual Plan (1997-98) have been prepared on the basis of a perspective. the main social direction and objective behind this perspective has been to assist, within the limited powers of the State Government, the increase in employment generation as far as possible, through efficient enhancement in levels of production in various sectors of the State economy. This requires that, in the spheres of infrastructure and social services, characterised by economic externalities and properties of public goods, there should be social action that is feasible in the State. This social action can be initiated by the State Government, the Panchayats or municipalities, and in some cases, even by organised group efforts of local people in coordination with the planning objective and process. At the same time there should be in the relevant spheres in the State, a persistent move towards equal competition.
Development and Planning Department Government of West Bengal